Differences in the Abilities to Mechanically Eliminate Activation Energies for Unimolecular and Bimolecular Reactions - Kochhar, Gurpaul S. (Sci Rep, 2016)
Mechanochemistry, i.e. the application of forces, F, at the molecular level, has attracted significant interest as a means of controlling chemical reactions. The present study uses quantum chemical calculations to explore the abilities to mechanically eliminate activation energies, ΔE(‡), for unimolecular and bimolecular reactions. The results demonstrate that ΔE(‡) can be eliminated for unimolecular reactions by applying sufficiently large F along directions that move the reactant and/or transition state (TS) structures parallel to the zero-F reaction coordinate, S(0). In contrast, eliminating ΔE(‡) for bimolecular reactions requires the reactant to undergo a force-induced shift parallel to S(0) irrespective of changes in the TS. Meeting this requirement depends upon the coupling between F and S(0) in the reactant. The insights regarding the differences in eliminating ΔE(‡) for unimolecular and bimolecular reactions, and the requirements for eliminating ΔE(‡), may be useful in practical efforts to control reactions mechanochemically.